Workaholism among a sample of turkish managers and professionals: An exploratory study - Burke, R. J.; Köksal, H. (PSYCHOLOGICAL REPORTS, P O BOX 9229, MISSOULA, MT 59807 USA, 2002)
This exploratory study attempted to replicate previous North American research on workaholism and the relationship of workaholism components proposed by Spence and Robbins to potential antecedents and consequences Data were obtained from 60 managers and professionals in Istanbul using anonymous questionnaires These questionnaires contained measures previously used in North America translated into Turkish Most measures had acceptable internal consistency reliability and the pattern of findings were generally consistent with previous North American results However, two of the three measures of workaholism components did not produce acceptable reliabilities, which suggests reconsideration of these specific measures and their items.
Keywords: UNDERSTANDING WORKAHOLISM; PERFORMANCE